Geopolitical Competition Among Great Powers and ASEAN’s Policy Preference - Ousaphea Chea (European Scientific Journal, ESJ, 2023)
The United States has long been a security ally and economic partner of ASEAN members. The strengths of the U.S.-ASEAN partnership include cooperation on regional security, economic growth, and people-to-people ties. The United States also supports ASEAN's efforts to promote regional cooperation and integration through mechanisms such as the ASEAN Regional Forum and the East Asia Summit. Moreover, the United States has demonstrated its commitment to maintaining a free and open Indo-Pacific region, which is consistent with ASEAN's own desire for a rules-based regional order. Due to its strategic presence in the Asia-Pacific region, the United States is considered to play a very important role in ASEAN's soft balance against China. ASEAN's hedging approach and bandwagoning are no longer relevant in the context of rising competition between China and the United States. This paper will explain the causes of China and ASEAN's lack of political and security cooperation. By combing and evaluating current literature discussing the political and security cooperation between ASEAN and ASEAN countries with China and the United States. ASEAN's security policy against China, in particular. This paper's main research method is to explain the adjustment of ASEAN's policy toward China in the context of great power geopolitics through the soft balance theory by analyzing the political and security cooperation between ASEAN and China and the United States, as well as the weapons imported by ASEAN countries from China and the United States.